Metastatic signet ring cell carcinoma of unknown primary source - O'Kane, Dermot (BMJ Publishing Group, 2014)
An elderly man presented to the emergency department following a motorbike accident. He had sustained chest injuries and a grade 1 splenic laceration. He had a moderate amount of free fluid and some omental standing on trauma CT, which was concerning for occult malignancy. A follow-up CT 4 weeks later showed a marked progression of the ascites and omental stranding. Ascitic tap was negative for malignancy. Tumour markers were normal. The patient developed a proximal small bowel obstruction which appeared to be related to this omental caking in the left upper quadrant on CT. Gastroduodenoscopy did not display any mass lesion. There was an external compression of the duodenum which could not be traversed with the scope. Laparoscopy showed a widespread peritoneal carcinomatosis. Biopsies of the omentum and peritoneum confirmed metastatic signet ring cell carcinoma (cytokeratin 7 and cytokeratin 20 positive). The patient was palliated but died 2 weeks after his diagnosis.